Genomic characterization and multidrug resistance of Pseudomonas aeruginosa isolated from peregrine falcons in Saudi Arabia: A One Health perspective - Ali Wahdan; Mahmoud Mohamed; Mahmoud M. Elhaig; Mohammed Al-Rasheed; Ehab M. Abd-Allah (Veterinary World)
Background and Aim: Pseudomonas aeruginosa is a multidrug-resistant (MDR) zoonotic pathogen increasingly implicated in infections in both humans and animals, including avian species. Raptors, particularly peregrine falcons, are vulnerable due to their exposure to diverse environments and intensive management practices. This study aimed to identify P. aeruginosa isolates from peregrine falcons in Saudi Arabia and to characterize their genomic features, phylogenetic relationships, and antimicrobial resistance (AMR) profiles using whole-genome sequencing (WGS).